Pengaruh Model Problem Based Learning Berbantuan PhET terhadap Keterampilan Berpikir Kritis Siswa pada Materi Getaran dan Gelombang - Anita Nur Izzati; Ni Made Pujani; Luh Mitha Priyanka (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
This study aims to examine the effects of applying a Problem-Based Learning (PBL) method combined with PhET simulation tools on enhancing critical thinking skills among eighth-grade students at SMP Negeri 4 Singaraja when learning vibration and wave topics. It adopted a quasi-experimental approach with a Pretest-Posttest setup and non-equivalent control group design. The participant cohort comprised 75 students distributed across two groups: the treatment group (n=38) who engaged in learning activities using PBL supplemented by PhET simulation, and the comparison group (n=37) who received PBL instruction without PhET simulation support. Data collection was conducted through essay-type assessment instruments containing 7 questions designed to evaluate critical thinking competencies based on Ennis' theoretical framework. Data processing employed descriptive statistical analysis, N-Gain Score computation and ANCOVA testing were conducted at a 0.05 significance level. Results showed the treatment group's average Posttest score at 84, compared to 66 for the control group. The ANCOVA produced an F-value of 103.701 (p < 0.001), confirming a statistically significant difference in critical thinking skills between the groups. The adjusted mean Posttest scores were 83.99 for the treatment group and 66.01 for the comparison group, reflecting a differential of 17.99 points. Consequently, the findings substantiate that the integration of PBL with PhET simulation demonstrates greater effectiveness in fostering students' critical thinking skills in comparison to conventional PBL implementation without technology-enhanced simulation assistance.